The Hebrew Bible Scapegoat: Complicating a Frazerian Typology - Smith, Caroline (New Age Movements, Occultism, and Spiritualism Research Library, 2023)
Although now methodologically outdated, The Golden Bough is credited with making decisive the scapegoat’s meaning as the innocent surrogate victim who is blamed and punished for the deeds of others. This victim’s namesake, the Hebrew Bible scapegoat that features in a collective rite of atonement (Leviticus 16), is regularly conceptualized in just these terms. Indeed, the practice of ascribing blame to an innocent party, or scapegoat, often entailing harm, mistreatment, and even death, is commonly understood to trace its origins to this Biblical rite in which the sins of the Israelites are symbolically placed upon a goat which is led to the wilderness in an act that ritually separates the people from their impurity. Yet the Biblical scapegoat was neither blamed, harmed, nor punished. Instead, it was a healing device, one whose meaning has become lost. My research aims to retrieve its original healing character, in part by proposing a critical corrective to its conceptualisation as Frazer’s surrogate victim. But this is not to argue that the Hebrew Bible lacks such a victim. Regularly overlooked in discourse about the Biblical scapegoat and its putative relationship with the practice that Frazer charts in The Golden Bough are events that follow the fall of Jericho (Joshua 7) in which people and animals appear to pay with their lives for the deeds of others. Those expecting to encounter the Frazerian scapegoat in its traditionally assigned home in the book of Leviticus may well be disappointed, but evidence for the practice whose name Frazer popularized may permeate the pages of Joshua.
1 video file. ms150-40-010_smith-caroline_bible-scapegoat_2023-02-11.mp4 .mp4 399.17 MB 418,558,021
Keywords: Scapegoat--Religious aspects--Judaism; Scapegoat in literature; Bible. Joshua--Criticism and interpretation; Bible. Old Testament--Criticism and interpretation; Frazer, James George, 1854-1941. Golden bough. Abridged; Video recordings